Immunity Against Bacterial Infection of the Central Nervous System: An Astrocyte Perspective - Geyer, Sohair; Jacobs, Muazzam; Hsu, Nai-Jen (Frontiers in Molecular Neuroscience, 2019)
Bacterial infection of the central nervous system (CNS) is a severe and life-threatening condition with high mortality, and it may lead to permanent neurological deficits in survivors. Increasing evidence indicates that astrocytes, as the most abundant CNS glial cell population, regulate innate and adaptive immune responses in the CNS under pathological conditions in addition to their role in the maintenance of CNS homeostasis and neuronal function. Following antigen recognition, astrocytes participate in the initiation of innate immune responses, and prompt an adaptive immune response to recruit peripheral immune cells. Investigations have been conducted to understand the immunological role of astrocytes in CNS disease and injury, however their part in bacterial infections of the CNS has not been fully evaluated. A better understanding will permit the identification of successful therapeutic targets for an improved prognosis and disease outcome.